Emerging Technologies in 5G Networks for IoT-Based Smart Healthcare: A Review - Fathia Adwep,; Mabroka Bobreeg, (AlQalam Journal of Medical and Applied Sciences, 2025)
Extensive efforts have been undertaken by governments, research institutes, and telecommunications corporations to expand the availability of fifth‑generation (5G) technology. Closely integrated with the Internet of Things (IoT), 5G enables automation and facilitates large‑scale data collection aimed at improving quality of life. This paper presents an overview of 5G and IoT technologies, highlighting common architectural designs, typical IoT deployments, and persistent challenges. Particular attention is given to interference in wireless applications, with a focus on issues specific to 5G and IoT, as well as potential strategies for mitigation. The study underscores the importance of managing interference and enhancing network efficiency to ensure reliable communication among IoT devices, which is essential for the effective operation of enterprise systems. For organizations that rely on these technologies to improve customer satisfaction, reduce downtime, and increase productivity, the findings provide valuable insights. Finally, the paper emphasizes the potential of network convergence and advanced services to enhance internet speed and accessibility, thereby fostering new opportunities for innovative businesses and applications.